(untitled) (Raparin Journal of Humanities (RJH), 2024)
As Poets become more sensitive and inspired to write Poems in the fall, this season is called Poets’ season. The climate change in this season affects the psychology of the poets and makes them feel (loneliness, departure, old age and death…etc.) even more and as a result their poems lean more towards these characteristics and would move them towards writing poems that embody characteristics of the fall and carrying some terms and tools that emanate from natural phenomena of the fall like (falling dead leaves, wind, foreignness, sadness, departure and death…etc.). Such entities become the tools of the fall-poems and would be utilized for different meanings and purposes. The existence of fall-poems can be detected in ancient Kurdish poems and become clearer with Besarany and extends through Mawlawy up till modern-classic, modern and contemporary poets. The basics of the romantics can be observed in fall-poems, which is a wide field giving free reign for this type of poem to extend its wings and show its aspects including ancient and modern poems. This Paper is divided into two sections; in the first section, example of fall-poems from poets like: (Besarany, Naly, Salim, Kurdy, Mahwy) are presented with the clarification of fall-related tools used in them. As for the second section, the history of the emergence of Kurdish Romantic Poems and Kurdish Romantic Characteristics has been presented, as well as elucidation of three poems by (Besarany, Hemin, and Hasib Qaradaghy) and identifying the romantic foundations found in them. And lastly, the conclusion is presented.